2008
DOI: 10.1111/j.1572-0241.2007.01543.x
|View full text |Cite
|
Sign up to set email alerts
|

Grasp or Brush for Biliary Sampling at Endoscopic Retrograde Cholangiography? A Blinded Randomized Controlled Trial

Abstract: Biliary sampling at ERC using a dedicated basket provided a significantly higher sensitivity for cancer detection than brushing; presampling stricture dilation significantly increased sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 23 publications
2
26
0
1
Order By: Relevance
“…However, this observation has not been consistently shown in the literature [1]. Several studies have suggested that the increased exfoliation of tumor cells due to stricture manipulation may increase the diagnostic yield of biliary brush cytology [23-25, 28]. Farrell et al [28] found that stricture dilatation to 10 French and endoscopic needle aspiration significantly increased both the sensitivity and specificity of biliary brushing cytology.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, this observation has not been consistently shown in the literature [1]. Several studies have suggested that the increased exfoliation of tumor cells due to stricture manipulation may increase the diagnostic yield of biliary brush cytology [23-25, 28]. Farrell et al [28] found that stricture dilatation to 10 French and endoscopic needle aspiration significantly increased both the sensitivity and specificity of biliary brushing cytology.…”
Section: Discussionmentioning
confidence: 91%
“…However, such findings have not consistently been demonstrated in the literature, and several authors have reported that stricture dilatation before brush cytology does not increase the sensibility of the technique, although the reasons for that discrepancy remain unknown [1, 34]. Compared with conventional brush cytology, the use of a dedicated basket has been associated with increased sensitivity for cancer detection in a randomized trial [23]. However, in a recent study, biliary sampling with a conventional Dormia basket was found to be comparable to conventional brush cytology in detecting malignant bile duct stricture [24].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…To improve the sensitivity and specificity, many investigators employ various sampling techniques, new devices, the cell block method and molecular methods, such as k-ras point mutation analysis or FISH [7,8,9,10,11,12,13,14,15,16,17,18,19,20]. In some hospitals, to facilitate smear sampling, rapid on-site evaluation is used to prevent air-drying and insufficient sampling [20].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have attempted to increase sensitivity and specificity by the use of grasping instruments [3]. A computer-based digital analysis, DNA image cytometry (ICM-DNA), assesses quantitative chromosomal changes, referred to as DNA-ploidy, in the nuclei of atypical cells in reference to normal DNA values determined with unequivocally benign nuclei in the same smear.…”
mentioning
confidence: 99%